Trends in the ICTs Toward Tourism, Hospitality and Gastronomy - Mejía, Jezreel; Cardona Reyes, Hector; Álvarez-García, José; del Río-Rama, María de la Cruz; Esparza-Huamanchumo, Rosse Marie (Lecture Notes in Networks and Systems, 2025)
XIII, 250 p. 43 illus., 35 illus. in color.